Philopatry and Regional Connectivity of the Great Hammerhead Shark, Sphyrna mokarran in the U.S. and Bahamas - Guttridge, Tristan L.; Van Zinnicq Bergmann, Maurits P. M.; Bolte, Chris; Howey, Lucy A.; Finger, Jean S.; Kessel, Steven T.; Brooks, Jill L.; Winram, William; Bond, Mark E.; Jordan, Lance K. B.; Cashman, Rachael C.; Tolentino, Emily R.; et al. (Frontiers in Marine Science, 2017)
A thorough understanding of movement patterns of a species is critical for designing effective conservation and management initiatives. However, generating such information for large marine vertebrates is challenging, as they typically move over long distances, live in concealing environments, are logistically difficult to capture and, as upper-trophic predators, are naturally low in abundance. As a large bodied, broadly distributed tropical shark typically restricted to coastal and shelf habitats, the great hammerhead shark Sphyrna mokarran epitomizes such challenges. Highly valued for its fins, it suffers high bycatch mortality coupled with conservative fecundity, and as a result, is vulnerable to over-exploitation and population depletion. Although there is very little species specific data available, the absence of recent catch records give cause to suspect substantial declines across its range. Here, we used biotelemetry techniques (acoustic and satellite), conventional tagging, laser-photogrammetry, and photo-identification to investigate; the level of site fidelity, and or residency for great hammerheads to coastal areas in the Bahamas and U.S. and the extent of movements and connectivity of great hammerheads between the U.S. and Bahamas. Results revealed large scale return migrations (3030 km), seasonal residency to local areas (some for 5 months), site fidelity (annual return to Bimini and Jupiter for many individuals) and numerous international movements. These findings enhance the understanding of movement ecology of the great hammerhead shark and have the potential to contribute to improved conservation and management.